Assessing glycation‐mediated changes in human cortical bone with Raman spectroscopy. Issue 8 (6th May 2018) - Unal, Mustafa; Uppuganti, Sasidhar; Leverant, Calen J.; Creecy, Amy; Granke, Mathilde; Voziyan, Paul; Nyman, Jeffry S.
Abstract : Establishing a non‐destructive method for spatially assessing advanced glycation end‐products (AGEs) is a potentially useful step toward investigating the mechanistic role of AGEs in bone quality. To test the hypothesis that the shape of the amide I in the Raman spectroscopy (RS) analysis of bone matrix changes upon AGE accumulation, we incubated paired cadaveric cortical bone in ribose or glucose solutions and in control solutions for 4 and 16 weeks, respectively, at 37°C. Acquiring 10 spectra per bone with a 20X objective and a 830 nm laser, RS was sensitive to AGE accumulation (confirmed by biochemical measurements of pentosidine and fluorescent AGEs). Hyp/Pro ratio increased upon glycation using either 0.1 M ribose, 0.5 M ribose or 0.5 M glucose. Glycation also decreased the amide I sub‐peak ratios (cm −1 ) 1668/1638 and 1668/1610 when directly calculated using either second derivative spectrum or local maxima of difference spectrum, though the processing method (eg, averaged spectrum vs individual spectra) to minimize noise influenced detection of differences for the ribose‐incubated bones. Glycation however did not affect these sub‐peak ratios including the matrix maturity ratio (1668/1690) when calculated using indirect sub‐band fitting. The amide I sub‐peak ratios likely reflected changes in the collagen I structure. Abstract : Accumulation of advanced glycation end‐products (AGEs) within bone matrix is thought to adversely affect fracture resistance. Yet, there is no non‐destructive method to assess effects of AGEs on collagen I structure. Herein, we demonstrate the use of Raman spectroscopy to detect glycation‐mediated changes in human bone ex vivo and highlight the effects of data collection and processing on probing spectral changes. Amide I sub‐peak ratios are sensitive to AGE accumulation.